Estimating the incidence of abortion: a comparison of five approaches in Ghana. Issue 4 (2nd April 2020) - Keogh, Sarah C; Otupiri, Easmon; Chiu, Doris W; Polis, Chelsea B; Hussain, Rubina; Bell, Suzanne O; Nakua, Emmanuel K; Larsen-Reindorf, Roderick
Abstract : Introduction: Induced abortion estimates are critical for reproductive health programming. In countries like Ghana where abortion is somewhat legally restricted and highly stigmatised, official records are incomplete and different approaches are needed to measure abortion incidence. We conducted a study in Ghana to test five methodologies for estimating incidence: direct reporting, the list experiment, the confidante method, the Abortion Incidence Complications Method (AICM) and a modified AICM. Methods: The direct reporting, list experiment and confidante method were implemented through a nationally representative community-based survey (CBS) of 4722 women. The AICM used data from a nationally representative health facilities survey (HFS) and a knowledgeable informant survey. The modified AICM combined CBS and HFS data. For each approach, we calculated abortion incidence nationally and for Ghana's three ecological zones and conducted checks to determine the most internally valid approaches. Results: National incidence estimates ranged from 27 per 1000 (AICM) to 61 (confidante method). The Northern zone displayed lower rates than the other two zones for all approaches. Validity and reliability checks found that the list experiment was invalid. The approaches that stood up to the internal validity checks and were most reliable were the direct reporting, confidante method and modified AICM. These approaches provide lower and upper bound estimates for the abortion rate, and the mean of the estimates from the three approaches yields a final abortion rate of 44 per 1000 and an unintended pregnancy rate of 103 per 1000. Conclusions: Comparing five approaches to estimating abortion enabled cross-validation of findings and highlighted strengths, pitfalls and requirements of each approach that can inform abortion estimation in other settings.